When shoppers don't have enough self-control resources: applying the strength model of self-control. Issue 4 (12th June 2017) - Yim, Mark Yi-Cheon
Abstract : Purpose: This study aims to empirically test and explain shoppers' purchase behavior in a retail store by applying the strength model of self-control. Design/methodology/approach: A pretest was used to identify shoppers' purchase change behavior based on 500 average shoppers, followed by a main study based on another set of 166 average shoppers, to test the proposed hypotheses. Findings: As shoppers stay shorter in a grocery store, they tend to change their purchase decisions more frequently. In addition, this study results reveal that three behavioral variables, namely, shoppers' changed purchase decisions, shopping duration and walking distance, significantly predict their overall spending. Research limitations/implications: The findings from the current study are limited to a designated superstore conducted for this study only. From a managerial viewpoint, the author suggests that giving shoppers more choice options and encouraging them to spend more time and walk further in a grocery store, depleting their self-control resources, can be an effective strategy in increasing sales. Yet, excessive efforts for these ideas can also cause shoppers' massive returns once they return to the normal state with sufficient self-control resources. Originality/value: The current study empirically confirms the applicability of the strength model of self-control through field studies designed to increase the external validity of the findings. To the best of the author's knowledge, this research is the first to apply and empirically test the strength model of self-control in the field to explain shopper behavior and highlight the importance of understanding shoppers' changed purchase decisions.